Minimally invasive treatment of tibial plateau depression fractures using balloon tibioplasty: Clinical outcome and absorption of bioabsorbable calcium phosphate cement. (3rd March 2020) - Greimel, Felix; Weber, Markus; Renkawitz, Tobias; Voellner, Florian; Freude, Thomas; Grifka, Joachim; Craiovan, Benjamin
The exact reconstruction of the tibial plateau and articular surface is the main operative aim in the treatment of tibial plateau depression fractures. For selected cases, a novel technique with the use of balloon tibioplasty in combination of bioabsorbable calcium phosphate cement is available. In this study, the first objective was to answer the question whether the clinical outcome parameters after balloon tibioplasty are comparable to open reduction procedures described in the literature. Secondly, we asked whether the cement absorption is safe in relation to adverse effects like osteolysis and measured the absorption ability during the bone conversion process in the proximal tibia bone. Eight patients (mean age 54 years; 4 males and 4 females) received the abovementioned surgical procedure. Mean follow-up period was 27 months. This study evaluated clinical outcome and radiological measured cement absorption within the postoperative course. Cement absorption was measured on X-rays and calculated based on the greatest extend on anterior–posterior and lateral view radiographs just after the operation on the latest available follow-up. WOMAC score showed a mean of 93. Radiologic absorption was 1/5 at a mean of 18 months. No osteolysis reaction was seen surrounding the cement. This far, promising clinical and radiological results have been shown with WOMAC scores comparable to the results of noninjured knees. The indication for this relatively new technique is restricted to isolated depression fractures. It is a useful tool to facilitate the reduction of select depressed tibial fractures. The radiologic absorption effect seems to be quite fast in bone remodeling and safe without any osteolysis or osseous reaction.